Leadership Patterns And Its Relationship With The Customer's Satisfaction - Ali Ramadan Musbah; Nasser Ahmed Habtoor; Ahmed Abdulmalik (Australian Society For Commerce Industry & Engineering, 2024)
This study aims at investigating the relationship between the administrative leading patterns (bureaucracy, democracy and free) and customer satisfaction through (physical quality and handling of the service),where the study sample represented in the Libyan customers at commercial Libyan banks, the number was 220 item. In order to achieve the goal of the study, data and information was collected from the sample through questionnaire. It was then processed statistically using statistical software (SPSS) andthe multiple inclination linear analysis. One of the most important findings of the study that there is a trace of the pattern of democracy administrative leadership and free on the customer’s satisfaction, while there is no relationship between the pattern of bureaucracy and customer’s satisfaction